Microencapsulation of Erythrocytes Extracted from Cavia porcellus Blood in Matrices of Tara Gum and Native Potato Starch - Ligarda Samanez, Carlos A. (2022)
Ferropenic anemy is the leading iron deficiency disease in the world. The aim was to encapsulate erythrocytes extracted from the blood of Cavia porcellus, in matrices of tara gum and native potato starch. For microencapsulation, solutions were prepared with 20% erythrocytes; and encapsulants at 5, 10, and 20%. The mixtures were spray-dried at 120 and 140 ◦C. The iron content in the erythrocytes was 3.30 mg/g and between 2.32 and 2.05 mg/g for the encapsulates (p < 0.05). The yield of the treatments varied between 47.84 and 58.73%. The moisture, water activity, and bulk density were influenced by the temperature and proportion of encapsulants. The total organic carbon in the atomized samples was around 14%. The particles had diverse reddish tonalities, which were heterogeneous in their form and size; openings on their surface were also observed by SEM. The particle size was at the nanometer level, and the zeta potential (ζ) indicated a tendency to agglomerate and precipitation the solutions. The presence of iron was observed on the surface of the atomized by SEM-EDX, and FTIR confirmed the encapsulation due to the presence of the chemical groups OH, C-O, C-H, and N-H in the atomized. On the other hand, high percentages of iron release in vitro were obtained between 88.45 and 94.71%. The treatment with the lowest proportion of encapsulants performed at 140 ◦C obtained the best results and could potentially be used to fortify different functional foods.